Pengembangan Sistem Informasi Manajemen Distribusi Ternak berbasis Website (Studi Kasus: Supplier Bebek Prembun) - Nonny Windarti; Denny Sagita Rusdianto; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Supplier Bebek Prembun is a business in the field of providing ducks to meet the raw material needs of restaurants and slaughterhouses. Purchase transactions of ducks from traders and sales transactions to restaurants with accounts receivable payment systems. Bill payments that are not charged become a problem when the restaurant is late in making payments, because it will hinder the process of buying ducks from traders. The daily turnover of ducks is very fast so it is difficult for Prembun Duck Suppliers to record incoming and outgoing money. Development of Livestock Distribution Management Information System Website Based Case Study of Supplier Bebek Prembun is expected to solve this problem. The system was developed by applying the waterfall model. Functional and non-functional requirements are obtained from the needs analysis process by conducting field observations and interviews. The design is made so that the implementation system is in accordance with the needs analysis. The system is implemented using the PHP programming language with the Laravel framework. The implemented system was tested by unit and integration testing using the white box method, validation testing using the black box method, and compatibility testing using sortite software. White box testing was carried out on 4 sample methods and the status resulted in valid. Black box testing was carried out on 42 functional requirements to produce all valid functionals. While the results of compatibility testing are that the implemented system can run well in various web browsers.